Definition of hue of different types of pokostivskiy granodiorite using digital image processing - Korobiichuk, Valentyn; Shamrai, Volodymyr; Iziumova, Oksana; Tolkach, Oleksandr; Sobolevskyi, Ruslan (Eastern-European Journal of Enterprise Technologies, 2016)
An important task of stone processing enterprises is decorativeness management of natural stone products. Among different ways to change the natural stone decorativeness parameters, stone polishing is the most common. Classification of the types of Pokostivskiy granodiorite of different hues is based on the characteristics of different types of stone after machining. However, information about the original color characteristics of stone blocks is needed for selecting the polishing technology. In the study of Pokostivskiy granodiorite blocks, the patterns of lightness changes in rough and polished samples of the types of Pokostivskiy granodiorite of different hues depending on the share of white minerals were identified. Before polishing, lightness and average share of white minerals for light, dark and very dark types of Pokostivskiy granodiorite are virtually unchanged. After polishing, lightness of different types of Pokostivskiy granodiorite changes respectively from 59.5 % to 69.4 % – for light types; from 59.0 % to 65.5 % – for dark types; from 58.8 % to 61.2 % – for very dark types. The developed method of determining the types of Pokostivskiy granodiorite of different hues using digital image processing will allow distinguishing rough blocks, different in lightness and hue, on stone processing enterprises. This will enable stone processing enterprises to select raw materials without prior processing and to choose the polishing technology for standardized products that are made of similar rocks.